An exploration of the state and status of nature awareness, appreciation and education in the Irish primary school system - MADDEN, PATRICK ANTHONY (Trinity College Dublin. School of Education. Discipline of Education, 2019)
Abstract This research explores the state and status of nature awareness, appreciation and education in the Irish primary system. The research was undertaken because personal observation, anecdotal evidence, media reports and literature seem to indicate that children today are not engaging deeply with nature both at home or at school. This perceived lack of engagement is a cause of concern in a time of increasing biodiversity depletion and environmental degradation. The research design consists of a mixed methods approach in which (1) mainly quantitative methods are used (a) to elicit the views of 219 practising primary teachers based in schools in the counties of all four provinces on the question, (b) the nature-knowledge of 253 first year ITE students based on the content that sixth-class pupils would be expected to be familiar with, and (c), the status accorded to nature by inspectors in 220 primary schools situated across the country. (2) Qualitative methods are mainly used (a) to elicit the views of six experienced external visitors to primary schools who are knowledgeable about nature. The research finds that nature awareness, appreciation and education in primary schools is in decline due to a variety of factors such as poor school-ground design, lack of knowledge of teachers, lack of time to engage children with this domain of learning especially in an outdoor framework and lack of emphasis on it in ITE and by significant stakeholders in primary education. These findings are significant because the literature constantly reiterates the fact that children?s meaningful engagement with nature is beneficial for their mental and physical health, their aesthetic and spiritual appreciation, and their creative, cognitive and emotional development.
APPROVED
Keywords: Nature education; Nature awareness; Nature appreciation; Natural environment; Nature; School gardening; Primary science education